Apprenticeships and the digital transition : modernising apprenticeships to meet digital skill needs - (:unkn) unknown (Publications Office of the European Union, 2024)
"Digital technologies are increasingly being adopted in a variety of occupations and sectors, meaning that workers need a solid set of digital skills. Ensuring that young people and adults have opportunities to develop the right digital skills is crucial in avoiding skills shortages and fostering productivity. Apprenticeship can help develop the right skills for the digital transition and can also benefit from the introduction of digital technologies in its delivery. This publication draws from practice and research that explore how skill needs are changing due to the digital transition, how this impacts apprenticeship systems, how apprenticeships can support and promote the transition, and how they can benefit for from effective technology adoption and use in their delivery in the school-based and workplace components." (editor; BIBB-Doku)
Keywords: I 2.2 Europa; G 2.2.2 Internet / Mediengesellschaft; G 2.2.1 Technologisierung; 370; 300; Berufsbildung; Berufsbildungspolitik; Europa; Digitalkompetenz; Digitalisierung; Lernen am Arbeitsplatz